The Use of Transmissibility Properties to Estimate FRFs on Modified Structures - R.A.B. Almeida; A.P.V. Urgueira; N.M.M. Maia (Shock and Vibration)
When deriving an experimental model from Frequency Response Functions (FRFs), it may happen that the measurement of certain FRFs is impossible. This may be an important issue, mainly in the field of condition monitoring and damage detection, since some points of interest may become inaccessible in operational conditions. In this circumstance, it is useful to have some tools that can provide the prediction of such dynamic information. The transmissibility concept, extended to a general multiple degree-of-freedom system, can play an important role to circumvent these situations. The authors have shown in previous works that the estimation of such FRFs can be made possible by invoking important properties associated with the transmissibility function. The objective of this work is to evaluate different sets of FRFs, estimated by using the transmissibility concept and its associated properties, in an actual continuous structure to which different patterns of structural modification are applied. A supplementary study in this work shows that some of the sets for applied forces/known responses can better estimate the FRF data.